Global Advances in Value-Based Payment and Their Implications for Global Health Management Education, Development, and Practice - Counte, Michael A.; Howard, Steven W.; Chang, Larry; Aaronson, William (Frontiers in Public Health, 2019)
ABSTRACT Global advances in health policy reform and health management education and practice need to be closely aligned in order to successfully change national health policies and improve the performance of health care delivery organizations. This paper describes the globally acknowledged need for incentive-based organizational performance and relevant implications for health care management education and practice.